Implementation of Halal Certification among Micro, Small, and Medium Enterprises MSMEs in the Night Culinary Market of Sungai Penuh City - M Ibrahim Aziz; Khatimul Fitri; Muhammad Ridha; Arpan Zaman; Saadatul Maghfira (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2026)
Halal certification is an official recognition process to ensure that products comply with halal standards through inspections of ingredients, production processes, and halal assurance systems conducted by LPPOM MUI. This study aims to examine the implementation of halal certification among MSMEs in the Night Culinary Market of Sungai Penuh City, including the socialization and supervision carried out by LPPOM MUI and the understanding of culinary entrepreneurs regarding halal certification regulations. Using a qualitative field research approach, data were collected through interviews and observations with street food vendors and related stakeholders. The findings show that the socialization and supervision conducted by LPPOM MUI and local government agencies have not effectively reached restaurant entrepreneurs in the Night Culinary Market, as the programs mainly target Islamic religious counselors and packaged food producers. As a result, most culinary business actors still have limited understanding of halal certification procedures. Therefore, stronger and more targeted socialization and supervision are needed to improve entrepreneurs’ awareness and understanding of halal certification